The Layered Aplite-Pegmatite Sheets of Kînâlik, South Greenland, - Windley, B.; Bridgwater, D. (Meddelelser om Grønland, 1965)
A series of low-dipping garnet-bearing interlayered aplite and pegmatite sheets is described from Kînâlik, South Greenland. The sheets are made up of three main rock types: rhytmically layered garnetiferous aplite, megacrysts of perthite-quartz intergrowth, and pegmatite layers. The relationships between these components suggest that the sheets are the result of a single injection of magma which has segregated into a dominantly aplitic portion towards the lower margin and pegmatite towards the top. The observation that veins of pegmatite cut the aplite but not vice versa suggests that the pegmatite remained in a fluid state longer than the aplite. The relationship between the perthite megacrysts and the layered aplite is discussed in detail and it is suggested that while perthite and aplite were form ed approximately simultaneously, in some cases the megacrysts continued to grow after the initial formation of the aplite. Recrystallisation and a partial redistribution of material after the formation of layering but before the final solidification of the body is put forward as an explanation for some of the features described.